Hubungan Antara Dukungan Keluarga dan Asupan Makan pada Pasien Kanker Payudara - Heni Pradiyati; Marthia Ikhlasiah (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2026)
Breast cancer is one of the diseases with a high incidence rate and has significant impacts on patients' physical, psychological, and social conditions. Family support plays an important role in the recovery process, including the fulfillment of nutritional needs. This study aimed to analyze the relationship between family support and dietary intake among breast cancer patients. A quantitative study with a cross-sectional design was conducted involving 30 respondents selected through purposive sampling. Data were collected using a family support questionnaire and the 24-hour food recall method. Data were analyzed using univariate and bivariate analyses with the Spearman Rank test at a significance level of 5%. The results showed that most respondents had good family support (50%) and adequate dietary intake (53.3%). Bivariate analysis revealed a significant positive relationship between family support and dietary intake (p < 0.001), indicating that better family support was associated with more adequate dietary intake among patients. These findings highlight the importance of the involvement of family members and healthcare professionals in providing support and nutrition education to improve the quality of life of breast cancer patients.